The Influence of Characteristics and Institutions on the Empowerment of Cocoa Agribusiness Farmer Groups in South Sulawesi, Indonesia - Bulkis, Sitti; Kaimuddin, Kaimuddin; Astari, Asti (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2023)
Agricultural development, specifically cocoa agribusiness, is largely determined by the human resource. When human resources possess high motivation, creativity, and the ability to develop innovation, agricultural development is significantly improved. This phenomenon shows the necessity to strive for empowerment of farmer for capacity improvement. Therefore, this study aimed to (1) describe the level of empowerment of individual farmer and their groups, and (2) analyze influence of individual characteristics of farmer, groups, and the role of counseling in empowerment of groups member. The analysis was carried out in Soppeng Regency, South Sulawesi, Indonesia, using a combined quantitative and qualitative design. A total of 70 respondents and 12 informants were included, consisting of farmer groups administrator, extension workers, and heads of estate services. Data collection was carried out through surveys and in-depth interviews. Meanwhile, data processing and analysis for this study used Structural Equation Modeling (SEM) Partial Least Square (PLS). The results showed that both farmer and groups empowerment were mostly in the medium category. Furthermore, characteristics of individuals, farmer groups, and the role of counseling significantly affected empowerment of members, including groups. Empowerment of farmer groups also influenced the success of cocoa agribusiness. These results showed that the development of cocoa agribusiness required high empowerment of individual farmer and groups as farmer institutions.